Preventif Hipertensi dan Diabetes Mellitus pada Usia Produktif di Kelurahan Sungai Besar - Ridha Hayati; Hilda Irianty (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Prevalensi of hypertension in indonesia according to the research and development of health ( balitbankes ) through from basic health research ( riskesdas ) 2018 now about 34,1 % where increase from preceding numbers in 2013 with the rest 25,8 %. The hypertension based on the prevalence of the measurement result to those age over or equal to as many as 18 in city Banjarbaru 32,83 %. In the year 2015 , indonesiaranked 7th top in the world to the total number of diabetics as many as 9.1 million people .In south kalimantan , prevalence of dm it is estimated that approximately 38.113 ( 1.4 % ) people of total population is more 14 years. The target and the outer covering of devotion isit can be used as a teaching lecture promoting the health and could increase as the application of science to the public. A method of activities are 3, first is the preparatory stageimplementation and evaluation. The outcome of the activities activities received responsevery such as the community because so far are still minimal interventions affecting cognitivethe people directly coupled with examination blood pressure and blood sugar. The conclusion of this activity ntusias his communities receive direct information on health especially a disease often happens in public as a preventive manner, early so the team havea good response devotion